Effects of ethephon and cold storage on ripening of ’Packham’s Triumph’ pears - Seibert, Eduardo; Barradas, Carlos Iguassú Nogueira; Araújo, Paulo Junqueira de; Bender, Renar João (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out in 1996 at the Estação Experimental Agronômica of the Universidade Federal do Rio Grande do Sul, located in Eldorado do Sul county, RS, and at the Embrapa-Centro de Pesquisa Agropecuária de Clima Temperado (CPACT), located in Pelotas county, RS, Brazil. The objective was to evaluate the effects of ethephon sprays and cold storage on ripening of 'Packham's Triumph' pears. Pear trees were sprayed with ethephon concentrations of 0, 12.5, 25, 50 on 100 ppm 26 days before harvest. After harvest, the pears were stored at -1,0ºC and 92-96% R.H. for 0, 10, 20, 40 or 80 days. After cold storage the pears were kept at room temperature for two or eight days to evaluate shelf life. Fruit firmness decreased with increasing storage periods and days at room temperature. Total soluble solids (TSS)/titratable acidity (TA) ratios increased over time, and were the result mainly of increasing contents of TSS than of the reduction of TA. Ethylene production was not significantly influenced by any concentration of ethephon sprays, though, production rates were higher the longer the cold storage period as well as days at room temperature.